Transcriptomic, Proteomic, and Bioelectrochemical Characterization of an Exoelectrogen Geobacter soli Grown With Different Electron Acceptors - Cai, Xixi; Huang, Lingyan; Yang, Guiqin; Yu, Zhen; Wen, Junlin; Zhou, Shungui (Frontiers in Microbiology, 2018)
The ability of Geobacter species to transfer electrons outside cells enables them to play an important role in biogeochemical and bioenergy processes. Our knowledge of extracellular electron transfer (EET) process in the genus Geobacter is mainly from the study of G. sulfurreducens, and in order to fully investigate the EET mechanisms in the genus Geobacter, other Geobacter species should also be considered. This study focused on the EET of Geobacter soli GSS01, which exhibited a capability of reducing insoluble Fe(III) oxides and generating electrical current comparable with G. sulfurreducens PCA. Electrochemical characterization, including cyclic voltammetry, differential pulse voltammetry and electrochemical in situ FTIR spectra, revealed that different redox proteins contributed to the electrochemical behaviors of G. soli and G. sulfurreducens. Based on comparative transcriptomics and proteomics analysis, OmcS was the most upregulated protein in both G. soli and G. sulfurreducens cells grown with insoluble Fe(III) oxides versus soluble electron acceptor. However, amount of proteins including OmcE and PilA that are previously reported as being important for EET in G. sulfurreducens were downregulated or unchanged in G. soli cells grown with insoluble electron acceptors versus soluble electron acceptor, and many proteins that were upregulated in G. soli cells grown with insoluble electron acceptors versus soluble electron acceptor, such as OmcN, are not important for EET in G. sulfurreducens. We also identified 30 differentially expressed small RNAs (sRNAs) in G. soli cells grown with different acceptors. Taken together, these findings help to understand the versatile EET mechanisms existed in the genus Geobacter and point to the possibility of sRNA in modulating EET gene expression.